Electron backscatter diffraction investigation of length‐fast chalcedony in agate: implications for agate genesis and growth mechanisms. Issue 1 (18th December 2012) - FRENCH, M. W.; WORDEN, R. H.; LEE, D. R.
Abstract: Agates of volcanic origin contain a range of silica minerals, with chalcedony and quartz arranged in concentric bands. Although agates are abundant worldwide, little is known about the genesis of their characteristic banding patterns. Current hypotheses suggest the bands result either from precipitation from convecting siliceous hydrothermal influxes or by in situ crystallization of a silica gel. This study combines the use of a variety of analytical techniques, including electron backscatter diffraction (EBSD), cathodoluminescence (CL), and Fourier transform infrared (FT‐IR) spectroscopy, to characterize the silica minerals present and investigate their spatial and crystallographic relationships in the banding arrangement. Microstructural and spectroscopic observations reveal that chalcedony bands are composed of amorphous silica that also contains nanocrystalline and later‐formed microcrystalline quartz. Nano‐ and microcrystalline quartz grew with a ‐axes perpendicular to the growth substrate, typical of length‐fast chalcedony. The bands formed as a result of discrete influxes of silica‐rich fluid. Within these individual bands, there is a sequence of minerals: chalcedony‐A (with amorphous silica and nanocrystalline quartz) → chalcedony‐MQ (with microcrystalline quartz) → quartz. This sequence is reflected in the degree of crystallinity, crystal orientations and water content and is analogous to a diagenetic cycle; the initial chalcedony portion of the band commences with amorphous silica with nanocrystalline quartz followed by fibrous microcrystalline quartz crystals; chalcedony then grades into larger equiaxial mesoquartz crystals. This paragenetic sequence suggests a viable model for the growth of chalcedony in agates.